Fitting & pattern alteration a multi-method approach to the art of style selection, fitting, and alteration - Liechty, Elizabeth G.; Rasband, Judith; Pottberg-Steineckert, Della (New York Fairchild Books, 2016)
"Fitting and Pattern Alteration: A Multi-Method Approach to the Art of Style Selection, Fitting, and Alteration, Third Edition, shows readers how to recognize, evaluate, and correct fit for 88 figure variations. This comprehensive guide presents proven methods of style selection, fitting, and alteration. The authors use a multi-level approach that is both logical and easy to follow, and each procedure is clearly identified and fully illustrated with a second color added to clarify the procedure and show directional measuring. Each figure is drawn to scale ensuring consistency and accuracy"--Provided by publisher.
Keywords: Dressmaking -- Pattern design; Clothing and dress -- Alteration